اثر المؤرخين المشارقة على نظائرهم المغاربة ابن عذارى المراكشي انموذجا - بن عيسى اسماء; د/ خامد عائشة (My University, 2023)
ملخص: تناولت الدراسة أثر المؤرخين المشارقة على نظائرهم المغاربة ومدى صلة الكتابة التاريخية لبلاد المغرب في بداياتها الأولى بالكتابة التاريخية المشرقية من حيث المناهج والمواضيع التي عرفوها وتطورها من خلال كتاب البيان المغرب في إختصار أخبار ملوك الأندلس والمغرب لإبن عذارى المراكشي. Abstract: The study dealt with the impact of Eastern historians on their Moroccan counterparts and the extent to which the historical writing of the Maghreb countries in its early beginnings relates to the Eastern historical writing in terms of the curricula and topics that they knew and developed through the book Al-Bayan Al-Maghrib in Abridged News of the Kings of Andalusia and Morocco by Ibn Adhari Al-Marrakshi الكلمات المفتاحية : التدوين التاريخي للمسلمين /المؤرخين المشارقة/المؤرخين المغاربة/إبن عذارى المراكشي